Different from Others? Jews as Slave Owners and Traders in the Persian and Hellenistic Periods - Olshanetsky, Haggai; Escojido, Yael (Sapiens ubique civis, 2020)
The subject of Jews as slave owners and traders throughout history received much greater attention in the last few decades. But there is no research that focuses on the Persian and Hellenistic periods and their relevant findings. This current article hopes to do exactly that. This article shows that Jews owned slaves and even traded them throughout the Persian period and during the Hellenistic period until the rise of the Hasmonean Kingdom. The slaves themselves were not only gentiles but also Jews, who received no special treat-ment from their co-religionists. Regarding the ownership of slaves, it was found that each Jewish owner treated his slaves differently, showing a huge gap between the biblical laws on the matter and the reality. The different texts and finds brought here are a testimony to the disregard of the Biblical laws on slaves, and the subsequent similarity between the Jews and their gentile neighbours in both ownership and trade of slaves.